ANALISIS FAKTOR YANG PALING DOMINAN DARI RASIO KEUANGAN YANG DAPAT MEMPENGARUHI KINERJA LABA BERSIH (STUDI KASUS PADA INDUSTRI FARMASI YANG GO PUBLIC TERDAFTAR DI BURSA EFEK INDONESIA) PERIODE 2009-2016 - Ahmadi Ahmadi; Akhmad Irwansyah Siregar (Universitas Batanghari Jambi, 2017)
This research is based on how a corporate work in accordance with the expected goals of the company, good long-term goal short-term and long term. the company is said to have good performance or not (in terms of financial management) can be measured by how, the company's ability to meet its obligations (debt) which will be due, how the company's ability to craft a structure funding, i.e. the comparison between debt and capital, how the company's ability to earn a profit, how the company's ability to develop as well as how the company's ability to manage the asset to its full potential. Mendapatakan gain/profit is the main goal of any company (corporate) established. Due to the success of any company or business units tremendously reflected by how capable the company gained profit. Other things that can be measured is whether the circumstances of how the company's liquidity at this time. If the company is in a State of barada illikuid are able to also contribute to profit at the company. Furthermore the company in meeting the need for working capital of course there are some policies, such as the sale of stock and debt policy or through loans (loan) or letter of offer beharga bonds (bond) as well as the instruments of other debt. In this case whether the debt has been taken to finance the company's already memberikkan impact on the acquisition of the company's profit. Dissamping that the company's current assets and additions to assets that appear on financial reports already provide growt against acquisition of keuantungan. This requires that the power of an existing asset have companies capable of contributing to the company to its full potential to achieve maximum profit or income. Therefore the above phenomenon inspired the author to create research that deals with how the company gain profit ability based on the conditions existing assets liquidity, sert debt policy which is whether It's been right and see where the most dominant factors which affected it. By using secondary data, using multiple linear regression analysis tools as well as based on the theories of toeri that exists, then the author wanted got the conclusion of testing theory – theory of tersebtu by taking objects on the company-the company that belongs on the pharmaceutical Industry 2009-2016 period.Keyword: rasio keuangan, laba bersih